Lipreading and covert speech production similarly modulate human auditory-cortex responses to pure tones. - Kauramäki, J; Jääskeläinen, I; Hari, R; Möttönen, R; Rauschecker, J; Sams, M (2010)
Watching the lips of a speaker enhances speech perception. At the same time, the 100 ms response to speech sounds is suppressed in the observer's auditory cortex. Here, we used whole-scalp 306-channel magnetoencephalography (MEG) to study whether lipreading modulates human auditory processing already at the level of the most elementary sound features, i.e., pure tones. We further envisioned the temporal dynamics of the suppression to tell whether the effect is driven by top-down influences. Nineteen subjects were presented with 50 ms tones spanning six octaves (125-8000 Hz) (1) during "lipreading," i.e., when they watched video clips of silent articulations of Finnish vowels /a/, /i/, /o/, and /y/, and reacted to vowels presented twice in a row; (2) during a visual control task; (3) during a still-face passive control condition; and (4) in a separate experiment with a subset of nine subjects, during covert production of the same vowels. Auditory-cortex 100 ms responses (N100m) were equally suppressed in the lipreading and covert-speech-production tasks compared with the visual control and baseline tasks; the effects involved all frequencies and were most prominent in the left hemisphere. Responses to tones presented at different times with respect to the onset of the visual articulation showed significantly increased N100m suppression immediately after the articulatory gesture. These findings suggest that the lipreading-related suppression in the auditory cortex is caused by top-down influences, possibly by an efference copy from the speech-production system, generated during both own speech and lipreading.